(untitled) (Baghdad Science Journal, 2024)
Pseudomonas aeruginosa is an opportunistic pathogen responsible for serious infections. At least three different exopolysaccharides, alginate, polysaccharide synthesis locus (Psl), and pellicle exopolysaccharide (Pel) make up the biofilm matrix in P. aeruginosa . The effect of temperature on the biofilm formation and gene expression was examined by microtiter plate and real-time quantitative polymerase chain reaction (qRT-PCR). To be able to determine the effect of temperature on biofilm formation and gene expression of P. aeruginosa, 303 clinical and environmental samples were collected. Pseudomonas aeruginosa was isolated from 61 (20.1%) and 48 (15.8%) of the clinical and environmental samples, respectively. The ability of clinical and environmental P. aeruginosa isolates to develop biofilm was observed in 86.9% and 85.42% of the isolates, respectively, distributed into strong, moderate, and weak biofilm producers. Moreover, gene expression for pslA, pelA and algD genes was estimated for clinical and environmental isolates, the clinical P. aeruginosa isolates showed the highest biofilm production and the highest gene expression of pslA, pelA and algD genes as compared to environmental isolates when temperature changed. In summary, both clinical and environmental isolates formed biofilm and carried psl A, pel A and alg D genes regardless of the intensity of the biofilm. Also, 37°C represented the best temperature for biofilm production.